The effects of the antecedents of ewom on tourists' decision-making: Perceived trust as a mediator - Saad AL-SAAD; Yahya A. ALZGHOUL; Ayman HARB (Tourism and Hospitality Management)
Purpose - This study aimed to examine the relationships between the utilitarian perceptions (information quality), hedonic perceptions (pleasure) and social perceptions (social interaction and homophily) of tourists in eWOM - on the one hand and their decision-making processes on the other. Furthermore, this study explored how these perceptions determine the mediating effect of trust in eWOM. Methodology/Design/Approach - A quantitative survey was conducted based on a random sample of American international tourists. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to analyse the collected data. Findings - The results demonstrate a significant influence of bridging social capital, homophily and perceived enjoyment on tourists’ decision making. Secondly, perceived trust was found to mediate the relationship between, on the one side, bridging social capital, information quality, and perceived enjoyment, and on the other, tourists’ decision making. Originality - Based on the Stimulus-Organism-Response (SOR) theory, this study developed a new integrated model of the relationships between the eWOM antecedents and tourists’ decision-making, with perceived trust acting as a mediator.